Applying the approach/avoidance framework to understand the relationships between social courage, workplace outcomes, and well-being outcomes. Issue 6 (2nd November 2019) - Howard, Matt C.
ABSTRACT: The current article heeds three prior calls to advance the study of courage. First, we replicate prior findings regarding the relationship of social courage and work outcomes, but we also investigate, for the first time, the relationship between social courage and well-being outcomes. Second, we apply the approach/avoidance framework to understand how social courage influences these outcomes. Third, approach and avoidance motivations are tested as mediators of the relationships of social courage with outcomes while controlling for established aspects of personality, conscientiousness and neuroticism. Two longitudinal studies show that approach motivation is a robust mediator between courage and both workplace and well-being outcomes, suggesting that courageous individuals achieve positive outcomes because they particularly value the benefits in such actions. Avoidance motivation was a less consistent mediator. Implications are discussed, but it should be emphasized that broader relationships of social courage can now be identified by applying the approach/avoidance framework.